Sexuality in men with urinary incontinence - summary of current knowledge - Skierkowska, Natalia; Prylińska, Monika; Husejko, Jakub; Wysocka, Oktawia; Gajos, Małgorzata; Bieniek, Daria; Topka, Weronika; Leśniak, Zuzanna; Olszewski, Bogusz; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2018)
Background: The problem of urinary incontinence is facing an increasing population of people. The problem of incontinence is troublesome for both women and men. Incontinence decreases the quality of sexual life. Men struggling with incontinence often have problems with erection and ejaculation. Materials and methods: Analysis of articles in the EBSCO and Google Scholar database using keywords: sexuality, incontinence, men, Results: Urinary incontinence affects both women and men. There are no specific criteria with which this ailment can be diagnosed. Therefore it is impossible to determine how frequent urinary incontinence actually is. It is estimated that it can affect 4-8% of the population around the World. The problem becomes more and more severe, as the number of affected patients grows each year. The urinary incontinence among men leads to sexual dysfunction, which causes various issues in private, professional and social life of such patients. Sexual dysfunction in male patients can lead to lower quality of life, what has a negative influence on their closest family and friends. Urinary incontinence in male patients can be treated pharmacologically or surgically. Only in case the non-invasive treatment fails, more radical methods are perused. Conclusions: Urinary incontinence more often affects women than men. It is a very embarrassing ailment, nevertheless patients under a proper treatment regain not only psychological but also sexual satisfaction. Urinary incontinence should not be a taboo topic, also among men patients. More research is needed to improve treatment program and support of such patients.